Effect of Time Transport on Mesenchymal Stem Cell Surface Markers: Unveiling the Influence of Cellular Translocation on Cellular Phenotype - Risky Chandra Satria Irawan; Naufal Ardjivani Arifin; Wicaksono, Hendi; Prasetio, Ardi (International Journal of Cell and Biomedical Science, 2023)
Mesenchymal stem cells (MSCs) hold great promise in regenerative medicine due to their ability to differentiate into multiple cell types and promote tissue repair. However, the effect of transportation time on the surface markers of MSCs remains understudied. This study investigated the impact of transportation time on MSC surface markers, specifically CD73, CD90, CD105, and hematopoietic lineage markers. MSCs were isolated from human umbilical cords and cultured. Flow cytometry analysis confirmed the expression of MSC surface markers. The MSCs were then subjected to simulated transportation for different time periods ranging from 0 to 24 hours at 2-8oC. After transportation, flow cytometry was used to analyze the expression of surface markers. The results showed that prolonged transportation time led to a decrease in the expression levels of CD73, CD90, and CD105, which are important markers for maintaining MSC functionality. Additionally, there was an increase in hematopoietic lineage marker expression. These findings suggest that transportation time can compromise the therapeutic potential of MSCs. Further investigation is needed to understand the underlying mechanisms responsible for the observed changes in surface marker expression. Optimization strategies, such as improved temperature control and protective agents, should be considered to mitigate the negative effects of prolonged transportation time. In conclusion, this study highlights the importance of considering transportation time and its impact on MSC surface markers in cellular therapy protocols. Understanding and addressing these effects are crucial for ensuring the quality and effectiveness of MSC-based therapies.